Odpowiedzi

2010-01-07T17:27:34+01:00
A)
3x + 2y = 13 / * 2
2x + y = 11 /* -3

6x + 4y = 26
-6x - 3y = -33
_______________
y = -7


3x + 2y = 13
2x + y = 11 /* -2

3x + 2y = 13
-2x - 2y = -22
___________________
x = -9

y = -7
x = -9


b)
5x+3y = 0
-x -2y = 7 / *5

5x+3y = 0
-5x -10y = 35
_______________
-7y = 35 / :-7
y = -5


5x+3y = 0 / *2
-x -2y = 7 / *3

10x + 6y = 0
-3x - 6y = 21
_____________
7x = 21 /:7
x = 3


y = -5
x = 3
1 5 1
2010-01-07T17:28:30+01:00
A) 3x + 2y = 13
2x + y = 11 / - 2x

3x + 2y = 13
y = 11 - 2x

3x + 2 (11 - 2x) = 13
3x + 22 - 4x = 13 / - 22
- x = - 9 / : (-1)
x = 9

27 + 2y = 13 / - 27
2y = - 14 / : 2
y = - 7


y = - 7
x = 9


_______________
b) 5x+3y = 0
-x -2y = 7 / + 2y

5x+3y = 0
- x = 7 + 2y / * (-1)

5x+3y = 0
x = - 7 - 2y

5(- 7 - 2y) + 3y = 0
- 35 - 10 y + 3y = 0 / + 35
- 7y = 35 / : (-7)
y =- 5

5x - 15 = 0 / + 15
5x = 15/ : 5
x =3


x=3
y= - 5



1 1 1
  • Xeo
  • Rozwiązujący
2010-01-07T17:29:22+01:00
A)3x + 2y = 13
2x + y = 11

3x + 2y = 13
y = 11 - 2x

3x + 2(11 - 2x) = 13
y = 11 - 2x

3x + 22 - 4x = 13
y = 11 - 2x

x = 13 - 22
y = 11 - 2x

x = - 9
y = 11 - 18

x = - 9
y = - 7

b) 5x+3y = 0
-x -2y = 7

5x + 3y = 0
-x = 7 - 2y // /-1

5x + 3y = 0
x = -7 + 2y

5(-7 + 2y) +3y = 0
x = -7 + 2y

-35 +13y = 0
x = -7 + 2y

y = 0
x = -7
1 5 1